AN INSIGHT INTO BREAST CANCER METASTASIS TO BONE: Life Sciences-Bio Chemistry - KOMAL TALREJA; ARCHANA MOON; SWATI KOTWAL (International Journal of Life Science and Pharma Research, 2022)
Breast cancer is the second leading fatal cancer in women following lung cancer. Out of three, two metastasize to bone. There are various factors (growth factors, genetic factors & some signaling pathways) responsible for metastasis, proliferation and colonization of cancerous cells to the bone. Once cancerous cells colonize to bone, they start a vicious cycle, which includes secretion of the osteolytic factors and tumor growth. The process of metastasis is a multistep process. Also, there are different types of breast cancer which includes Ductal carcinoma, lobular carcinoma, invasive ductal carcinoma and invasive lobular carcinoma. There are various therapeutics available against breast cancer, which focus on blocking osteoclast differentiation to prevent bone resorption. Various bioactive active compounds are reported to possess anticancer properties, which include Vitamin D, lysine, green tea extract, kampferol etc. They can act as nutritive therapy against cancer. This review deals with the risk factors and classification of breast cancer, mechanism of metastasis, current therapeutics available and their side effects.